2011
DOI: 10.1111/j.1469-8137.2011.03784.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular analysis of polyethylene glycol‐induced reduction of aluminium accumulation in the root tips of common bean (Phaseolus vulgaris)

Abstract: Summary• Aluminium (Al) toxicity and drought are two major stress factors limiting common bean (Phaseolus vulgaris) production on tropical acid soils. Polyethylene glycol (PEG) treatment reduces Al uptake and Al toxicity.• The effect of PEG 6000-induced osmotic stress on the expression of genes was studied using SuperSAGE combined with next-generation sequencing and quantitative reverse transcription-polymerase chain reaction (qRT-PCR) for selected genes.• Less Al stress in PEG-treated roots was confirmed by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 65 publications
(147 reference statements)
6
30
0
1
Order By: Relevance
“…The PEG-induced inhibition of Al accumulation in the root tips of common bean (Yang et al 2011c) was consistent with PEG-suppressed Al-induced expression of the multidrug and toxin extrusion (MATE) family protein gene (Fig. 3b) confirming the PEG-induced alleviation of Al toxicity at the molecular level.…”
Section: Root-growth Response Of Plants To Aluminium Toxicity and Drosupporting
confidence: 48%
See 4 more Smart Citations
“…The PEG-induced inhibition of Al accumulation in the root tips of common bean (Yang et al 2011c) was consistent with PEG-suppressed Al-induced expression of the multidrug and toxin extrusion (MATE) family protein gene (Fig. 3b) confirming the PEG-induced alleviation of Al toxicity at the molecular level.…”
Section: Root-growth Response Of Plants To Aluminium Toxicity and Drosupporting
confidence: 48%
“…Several CW-modifying proteins such as expansins, xyloglucan endotransglucosylase/hydrolases (XTHs), endoglucanases and pectin methylesterases (PMEs) play key roles in the modification of CW structure and thus porosity (recently reviewed by Sasidharan et al 2011). In Arabidopsis, microarray analysis indicated that most of the CW-associated genes including genes encoding those above-mentioned CW-modifying proteins are down-regulated under water deficit (Bray 2004) supporting the results generated from transcriptome analysis of the drought (PEG stress)-subjected root apices of common bean by SuperSAGE (serial of analysis of gene expression) (Yang et al 2011c). XTHs play key roles in modification of CW structure and extensibility through the cleavage and re-formation of bonds between xyloglucan chains (Bray 2004; Rose et al 2002).…”
Section: Cell-wall Porositymentioning
confidence: 63%
See 3 more Smart Citations